Leaving Your Car with Strangers: Informal Car Parkers and Improbable Trust in Mexico City. (September 2019) - de la Garza, Yuna Blajer
This article explores the case of informal car parkers in Mexico City, to whom drivers regularly entrust the keys to their vehicles. In contrast to literature on social trust that expects institutional trust and interpersonal trust to support one another, the article shows that interpersonal trust improbably arises in the context of corrupt and inefficient institutions. Coercive and market dynamics undergird the interactions among car parkers, police officers, and drivers, making possible the emergence of an informal market and noncontractual agreements. The exchange between car parkers and drivers depends on the performance of class—a performance that becomes legible and formulaic enough to appear safe, precisely because it coalesces classist tropes that are clearly distinct and recognizable. Interpersonal trust becomes possible not only despite class cleavages and institutional shortcomings but, paradoxically, because of them.